2021
DOI: 10.1513/annalsats.202006-729oc
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Telephone and Video Communication in the Intensive Care Unit during COVID-19

Abstract: Rationale: During the coronavirus disease (COVID-19) pandemic, many intensive care units (ICUs) have shifted communication with patients’ families toward chiefly telehealth methods (phone and video) to reduce COVID-19 transmission. Family and clinician perspectives about phone and video communication in the ICU during the COVID-19 pandemic are not yet well understood. Increased knowledge about clinicians’ and families’ experiences with telehealth may help to improve the quality of remote interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
141
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(149 citation statements)
references
References 19 publications
6
141
0
2
Order By: Relevance
“…In order to counteract this issue, video calls were introduced to facilitate communication between patients and family members when they were restricted from seeing their loved ones in the hospital. 18 - 20 However, in this study we found that many family members were shocked and felt more stressed after they saw their loved ones intubated, sedated, and connected to the ventilator.…”
Section: Discussionmentioning
confidence: 56%
“…In order to counteract this issue, video calls were introduced to facilitate communication between patients and family members when they were restricted from seeing their loved ones in the hospital. 18 - 20 However, in this study we found that many family members were shocked and felt more stressed after they saw their loved ones intubated, sedated, and connected to the ventilator.…”
Section: Discussionmentioning
confidence: 56%
“…ComunicoCOVID, 2020 , EU, 2021 , Kanaris, 2021 , Kennedy et al, 2021 , Scelsi, S., 2020 , WHO, 2021 , Ågård and Harder, 2007 .…”
Section: Uncited Referencesmentioning
confidence: 99%
“…Specifically, these suggestions included positioning the camera so that the family can see the patient and their surroundings, offering families the opportunity to ask questions about tubes and devices, and offering time for patients and families to interact without clinician participation. 24 …”
Section: Introductionmentioning
confidence: 99%
“…Specifically, these suggestions included positioning the camera so that the family can see the patient and their surroundings, offering families the opportunity to ask questions about tubes and devices, and offering time for patients and families to interact without clinician participation. 24 While these areas of improvement pertain to the particular model of virtual visiting used by Sasangohar 25 We know of the constellation of adverse phycological outcomes that can occur in ICU patients and their families, termed ICU trauma and post-intensive care syndrome-family respectively. [26][27][28][29][30][31] We also know that providing open and flexible visiting has the effect of reducing the risk of developing such outcomes.…”
Section: Introductionmentioning
confidence: 99%